A new day for CME/CPD in Canada: proceedings from the 1st Canada Regional Conference of the Global Alliance for Medical Education in Montreal, Canada. Issue 1 (1st January 2015) - Murray, Suzanne; Sullivan, Lisa
Abstract : The Global Alliance for Medical Education (GAME) is a not-for-profit organization founded in 1995, with the aim of advancing innovation in medical education. The 1st GAME Canada regional conference was held in Montreal on May 22, 2015, under the leadership of Suzanne Murray, who acted as programme chair, and GAME president Lisa Sullivan. The conference brought together a broad array of speakers and panellists, including experts from academic centres, health systems, accreditors, private organizations, and industry. Thirty-one key stakeholders participated in the event, demonstrating a strong commitment towards the improvement of best practice in continuing medical education (CME)/continuing professional development (CPD). The conference included diverse presentations providing opportunities for reflection and discussion throughout the day. The participants actively took part in stimulating discussions that covered a large range of topics, including the need for enhanced networking and opportunities to learn from others, the challenges of assessment and the potential solutions, interprofessional education and competencies, and, finally, the future of a Canadian CME/CPD organization.